ABNORMAL BLOOD LIPIDS LEVELS (DYSLIPIDEMIA) TREATMENT WITH ACUPUNCTURE METHOD - Rinjani, Anissa Maulina; Septriana, Maya; Herawati, Lilik (Journal of Vocational Health Studies, 2022)
Background: Dyslipidemia is an abnormal lipid metabolism characterized by an increase in total cholesterol, LDL (Low-Density Lipoprotein), triglycerides (TG), and a decrease in HDL (High-Density Lipoprotein). Increased levels of total cholesterol, TG, LDL, and decreased HDL levels can increase the risk of cardiovascular disease. According to TCM, dyslipidemia is categorized into "Tan Zheng” (phlegm syndrome), "Shi Zuo” (damp retention), "Xuan Yun” (vertigo), and "Fei Pang” (obesity). Purpose: The purpose of this review is to analyze the literature study on TCM within the treatment of dyslipidemia with different acupuncture methods and points. The primary data search was conducted using online e-resources (Google Scholar, Proquest, and Pubmed). Review: The results of the study should include at least one of the outcomes indicators for total cholesterol, TG, LDL, and HDL. The result there were 20 journals consisting of studies that used several acupuncture methods, manual  acupuncture  (AM),  electroacupuncture  (EA), moxa (MOK), auricular acupuncture (AA), Cupping (CUP), and found additional interventions  such as nutritional  interventions, and exercise; body points often used are Zusanli  (ST 36),  Fenglong (ST 40), Quchi (LI 11), Daheng (SP15), Zhongwan (CV 12), Qihai (CV 6), Guanyuan (CV 4), Sanyinjiao  (SP  6), Shenque  (CV  8),  Tianshu  (ST  25), and therefore for AA are Spleen (CO 13), Stomach (CO 4),  Shenmen (TF 4), and hunger point. Twenty journals showed a decrease in total cholesterol, TG, LDL levels, and an increase in HDL levels. Conclusion: In conclusion, all types of acupuncture methods can reduce total cholesterol, TG and LDL levels, and increase HDL levels.